Predicting Hope in Mothers of Intellectually Disabled Children Through Emotional, Psychological and Spiritual Factors - Amin Arabshahi; Faezeh Shahriari; Zabihollah Gharlipour (Health, Spirituality and Medical Ethics)
Background and Objectives: Mental retardation is associated with a lack of growth in various physical, mental, developmental, social, and educational dimensions. Many variables, such as emotional adjustment, psychological well-being, and spiritual beliefs are related to the hope of mothers with mentally retarded children. This research aimed to predict hope based on emotional adjustment, psychological well-being, and spiritual beliefs in mothers with mentally retarded children. Methods: The current research was descriptive-correlational. The statistical population of the research included 375 mothers with mentally retarded children who were selected from seven special education schools, occupational therapy centers, and an autism center in Qom City, Iran, in the 2022-2023 academic year. Convenience sampling was used, and Morgan’s table determined the sample size. Data collection tools were the Schneider et al.’s hope questionnaire, Bell’s emotional adjustment questionnaire, Riff’s psychological well-being questionnaire, and George’s spiritual beliefs questionnaire. Data were analyzed using SPSS software version 26, employing Pearson’s correlation test and multiple regression analysis. Results: The results of the regression analysis showed that all three variables of social adjustment, psychological well-being, and spiritual beliefs were significant predictors of hope (P<0.05). Specifically, emotional adjustment contributed 13.4%, psychological well-being contributed 12%, and spiritual beliefs contributed 13.8% to the variance in hope, with 95% confidence. Conclusion: The results of the study showed a significant relationship between hope, emotional adjustment, psychological well-being, and spiritual beliefs. Educational workshops are recommended to increase public understanding of intellectual disabilities. Authorities, specialists, and community workers should develop a structured and comprehensive program to raise awareness about the emotional adjustment, psychological well-being, and spiritual beliefs of these mothers within the community.